Hide or Show? Observability of Private Precautions Against Crime When Property Value is Private Information. (29th November 2018) - Baumann, Florian; Denter, Philipp; Friehe, Tim
Abstract: This article analyzes a contest in which property owners have private information about the property value they are trying to protect from thieves and determine whether or not to make their defense efforts observable. Using a framework with two property values and the intuitive criterion for equilibrium refinement, we show that a Perfect Bayesian equilibrium with observable defense effort always exists. Under restrictive circumstances, unobservable defense effort by both defender types may also constitute an equilibrium. In our framework, the classical distinction between observable and unobservable private precautions against crime thus results as an endogenous outcome.